Kinetic Study of 17α-Estradiol Activity in Comparison with 17β-Estradiol and 17α-Ethynylestradiol - Tereza Bosakova (Catalysts, 2021)
17α-estradiol (αE2), an endogenous stereoisomer of the hormone 17β-estradiol (E2), is capable of binding to estrogen receptors (ER). We aimed to mathematically describe, using experimental data, the possible interactions between αE2 and sperm ER during the process of sperm capacitation and to develop a kinetic model. The goal was to compare the suggested kinetic model with previously published results of ER interactions with E2 and 17α-ethynylestradiol (EE2). The HPLC-MS/MS method was developed to monitor the changes of αE2 concentration during capacitation. The calculated relative concentrations Bt were used for kinetic analysis. Rate constants k and molar ratio n were optimized and used for the construction of theoretical B(t) curves. Modifications in αE2–ER interactions were discovered during comparison with models for E2 and EE2. These new interactions displayed autocatalytic formation of an unstable adduct between the hormone and the cytoplasmic receptors. αE2 accumulates between the plasma membrane lipid bilayer with increasing potential, and when the critical level is reached, αE2 penetrates through the inner layer of the plasma membrane into the cytoplasm. It then rapidly reacts with the ER and creates an unstable adduct. The revealed dynamics of αE2–ER action may contribute to understanding tissue rejuvenation and the cancer-related physiology of αE2 signaling.